Preparation method of high temperature resistant ceramic adhesive based on parameter optimization

By real-time control of the baking time of high-temperature-resistant ceramic adhesive printing oil, and using Raman spectroscopy data to analyze the dissolution situation, the quality problems caused by improper baking time of the printing oil are solved, and the performance of the printing oil and adhesive is improved.

CN118308041BActive Publication Date: 2025-03-14HUNAN XIANGCI TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410733707.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2025-03-14
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

In the preparation process of high-temperature resistant ceramic adhesives, the baking time of the printing oil will affect its quality, resulting in poor viscosity and wettability.

Method used

By controlling the baking time in real time, using Raman spectroscopy data to analyze the dissolution of ethyl cellulose and terpineol, the clearness of the printing oil raw material solution is determined, and whether baking needs to be stopped based on the change in clarity.

Benefits of technology

Accurate control of the baking time in the oil preparation step is achieved, the quality of the oil is improved, and thus the performance of high-temperature resistant ceramic adhesive is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118308041B_ABST
    Figure CN118308041B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of ceramic adhesive preparation, and specifically to a method for preparing a high-temperature resistant ceramic adhesive based on parameter optimization, the method comprising: preparing synthetic powder: mixing, sieving, pre-synthesizing and ball-milling the raw material powder to obtain synthetic powder for standby use; preparing printing ink: putting the raw materials for preparing printing ink into a container, stirring and baking, and judging that a clear printing ink raw material solution is obtained based on the data overlap distribution in the Raman spectrum data of the printing ink raw material solution, analytically pure pine oil and ethyl cellulose, as well as the difference in spectral peak intensity and half-peak width, and stopping baking; cooling the container to obtain the printing ink for standby use; preparing high-temperature resistant ceramic adhesive: adding the synthetic powder and printing ink into a nylon ball mill for ball milling and sieving to obtain a high-temperature resistant ceramic adhesive. The present application aims to achieve the control of the baking time in the printing ink preparation step, improve the quality of the obtained printing ink, and thereby improve the quality of the high-temperature resistant ceramic adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic adhesive preparation, and in particular to a method for preparing a high temperature resistant ceramic adhesive based on parameter optimization. Background Art

[0002] High temperature resistant ceramic adhesive is an adhesive that can tightly connect two or more ceramic parts together. It can withstand high temperatures above 1000°C without falling off or cracking, and has excellent air tightness. It is widely used in semiconductor machinery parts, medical machinery parts, military aerospace, and high vacuum parts.

[0003] In the preparation process of high temperature resistant ceramic adhesive, printing ink, as an organic carrier of synthetic powder, has an important influence on the viscosity and wettability of the prepared high temperature resistant ceramic adhesive, so it is necessary to ensure the quality of the prepared printing ink. In the baking process in the printing ink preparation step, the baking time of the printing ink raw material solution is a key factor affecting the quality of the configured printing ink. If the baking time is too short, the ethyl cellulose in the printing oil raw material solution may not have enough time to completely dissolve, so that the printing oil raw material solution fails to reach the required clarity, affecting the transparency and color of the printing oil, while if the baking time is too long, it may cause excessive evaporation of pine oil, affecting the viscosity of the final printing oil. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a preparation method of a high temperature resistant ceramic adhesive based on parameter optimization to solve the existing problems.

[0005] The preparation method of the high temperature resistant ceramic adhesive based on parameter optimization of the present application adopts the following technical scheme:

[0006] The present application provides a method for preparing a high temperature resistant ceramic adhesive based on parameter optimization, the method comprising the following steps:

[0007] S1, preparation of synthetic powder: dry-mixing and sieving the raw powder; putting the sifted powder into a 99 porcelain container and placing it in a high-temperature electric furnace for pre-synthesis; placing the pre-synthesized powder into a nylon ball mill for ball milling, drying and sieving the ball-milled mixture to obtain synthetic powder for standby use;

[0008] S2, preparing the printing ink: putting the raw materials for preparing the printing ink into a container, stirring evenly, and baking until a clear printing ink raw material solution is obtained; cooling the container to obtain the printing ink for use; wherein the specific steps of real-time control of the baking time are:

[0009] (1) Collecting Raman spectral data of the ink raw material solution during the baking process of ink preparation, as well as Raman spectral data of ethyl cellulose and analytically pure pinene alcohol;

[0010] (2) Based on the data overlap distribution in the Raman spectral data of the printing ink raw material solution, analytically pure pinene alcohol and ethyl cellulose, the ethyl cellulose pixels in the Raman spectral data of the printing ink raw material solution are divided;

[0011] (3) determining the clarity of the printing ink raw material solution based on the peak intensity and half-peak width of the Raman spectrum peak corresponding to the ethyl cellulose pixel at different wavenumber positions in the Raman spectrum data of the printing ink raw material solution;

[0012] (4) judging whether it is necessary to stop baking the printing ink raw material solution based on the difference in the clarity of the printing ink raw material solution at the time before the current sampling time;

[0013] S3, preparation of high temperature resistant ceramic adhesive: adding synthetic powder and printing ink into a nylon ball mill, ball milling and sieving to obtain a high temperature resistant ceramic adhesive;

[0014] The judgment conditions for whether the ink raw material solution needs to stop baking include:

[0015] Calculate the coefficient of variation of the clarity of all printing ink raw material solutions obtained between the current sampling moment and the preset moment before, and use the reciprocal of the coefficient of variation at the current sampling moment as the baking completion coefficient at the current sampling moment;

[0016] Obtain a preset number of printing ink raw material solutions whose clarity meets the standard; wherein the printing ink raw material solutions whose clarity meets the standard are obtained by manual judgment;

[0017] The average value of the baking completion coefficients of all printing ink raw material solutions whose clarity meets the standard at the last sampling moment in the baking process is used as the baking completion threshold;

[0018] If the baking completion coefficient at the current sampling moment is greater than the baking completion threshold, the baking of the printing ink raw material solution is stopped;

[0019] The division process of the ethyl cellulose pixels in the Raman spectrum data of the printing ink raw material solution includes:

[0020] For each pixel in the Raman spectrum data of the printing ink raw material solution, ethyl cellulose and analytically pure pinene alcohol, based on the Raman spectrum peak distribution in the corrected Raman spectrum of each pixel, determine the Raman spectrum peak position sequence of each pixel;

[0021] All Raman spectrum peak position sequences of ethyl cellulose are averaged to obtain the Raman spectrum peak position enhancement sequence of ethyl cellulose; all Raman spectrum peak position sequences of analytically pure terpineol are averaged to obtain the Raman spectrum peak position enhancement sequence of analytically pure terpineol;

[0022] For any pixel in the Raman spectrum data of the printing ink raw material solution, the statistical result of the number of identical data points in the Raman spectrum peak position sequence of the any pixel and the Raman spectrum peak position enhancement sequence of ethyl cellulose is counted, and the ratio of the number of data points in the Raman spectrum peak position enhancement sequence of ethyl cellulose is recorded as the Raman peak overlap of ethyl cellulose in the any pixel; the statistical result of the number of identical data points in the Raman spectrum peak position sequence of the any pixel and the Raman spectrum peak position enhancement sequence of analytically pure pinene alcohol is counted, and the ratio of the number of data points in the Raman spectrum peak position enhancement sequence of analytically pure pinene alcohol is recorded as the Raman peak overlap of analytically pure pinene alcohol in the any pixel;

[0023] Classify any pixel whose Raman peak overlap of ethyl cellulose is greater than that of analytically pure pinene alcohol as an ethyl cellulose pixel;

[0024] The method for determining the clarity of the printing ink raw material solution comprises:

[0025] Assign values ​​of 0 to all data points at corresponding positions in the Raman spectrum peak position sequence of any pixel for all data points with a value of 1 in the peak position enhancement sequence of the Raman spectrum of the analytically pure terpineol, thereby obtaining a characteristic peak position sequence of ethyl cellulose of any pixel;

[0026] Re-assign the peak intensity and half-peak width of the Raman spectrum peak corresponding to the wave number position of each data point with a value of 1 in the characteristic peak position sequence of ethyl cellulose of any pixel, and record the assigned sequences as the characteristic peak intensity sequence and the characteristic peak width sequence of ethyl cellulose of any pixel, respectively;

[0027] Using the same method as the characteristic peak intensity sequence and the characteristic peak width sequence of ethyl cellulose of any pixel, the characteristic peak position sequence of ethyl cellulose of any pixel is replaced with the Raman spectrum peak position enhancement sequence of ethyl cellulose to obtain the spectrum peak intensity sequence and the spectrum peak width sequence of ethyl cellulose;

[0028] Determine the ethyl cellulose peak width increase of any pixel based on the ethyl cellulose characteristic peak intensity sequence and the ethyl cellulose characteristic peak width sequence of any pixel, and the spectral peak peak intensity sequence and the spectral peak peak width sequence of ethyl cellulose;

[0029] Calculating the average solubility of ethyl cellulose particles of all ethyl cellulose pixels in the Raman spectrum data of the printing ink raw material solution as the clarity of the printing ink raw material solution;

[0030] The method for determining the ethyl cellulose peak width increase comprises:

[0031] Calculate the cumulative sum of the ratios between the characteristic peak intensity sequence of ethyl cellulose of any pixel and all corresponding position data points in the peak intensity sequence of the spectrum peak of ethyl cellulose as the peak intensity increase of ethyl cellulose of any pixel;

[0032] Calculate the cumulative sum of the ratios between the characteristic peak width sequence of ethyl cellulose of any pixel and all corresponding position data points in the peak width sequence of the spectral peak of ethyl cellulose as the peak width increase of ethyl cellulose of any pixel;

[0033] The product of the ethyl cellulose peak intensity increase and the ethyl cellulose peak width increase of any pixel is taken as the ethyl cellulose particle solubility of any pixel.

[0034] Preferably, the raw materials and their mass percentages for preparing the synthetic powder in S1 are: 10 analytically pure aluminum oxide 20%, analytical pure silica 50 75%, analytical pure magnesium oxide 2 5%, analytical pure potassium nitrate 2 8%, analytical pure anhydrous sodium carbonate 0 5%.

[0035] Preferably, the ratio of material, balls and alcohol in the nylon ball mill in S1 is 1:2:1.

[0036] Preferably, the raw materials and their proportions for preparing the printing ink in S2 are: 1000ml of analytically pure pinene alcohol, 200mPa.S of ethyl cellulose, 20 40g, 50mPa.S ethyl cellulose 10 30 grams.

[0037] Preferably, the method for determining the Raman spectrum peak sequence includes:

[0038] Acquire a corrected Raman spectrum of the Raman spectrum of each pixel using a baseline correction algorithm;

[0039] Combining the Raman scattered light intensities of all wavenumber positions in the corrected Raman spectrum of each pixel into a Raman scattered light intensity sequence of each pixel;

[0040] Obtaining a Raman spectrum peak in the corrected Raman spectrum of each pixel, and obtaining a wavenumber position and a Raman scattered light intensity corresponding to each Raman spectrum peak;

[0041] The elements at the wavenumber positions corresponding to the Raman spectrum peak of each pixel in the Raman scattered light intensity sequence are assigned 1, and the remaining elements are assigned 0, and the sequence after the assignment is recorded as the Raman spectrum peak position sequence of each pixel.

[0042] Preferably, the ratio of synthetic powder and printing ink of the high temperature resistant ceramic adhesive in S3 is: synthetic powder 60 90g, printing ink 50 80 grams.

[0043] In the above scheme, the present application divides the pixel category of any pixel in the Raman spectrum data of the printing ink raw material solution based on the data overlapping distribution in the Raman spectrum data of the printing ink raw material solution, analytically pure pine oil and ethyl cellulose, and its beneficial effect is to reduce the interference of non-characteristic background signals, fluorescence signals and possible overlapping peaks in the Raman spectrum, and improve the distinction between the pixels corresponding to the ethyl cellulose substance and the analytically pure pine oil substance in the printing ink raw material solution in the Raman spectrum data; based on the peak intensity and half-peak width of the Raman spectrum peak corresponding to the ethyl cellulose pixel at different wavenumber positions in the Raman spectrum data of the printing ink raw material solution, the clarity of the printing ink raw material solution is determined, which has the following advantages: The beneficial effect is that the dissolution behavior of ethyl cellulose in the printing ink raw material solution can be identified and tracked through specific Raman spectral peaks, and the actual dissolution of ethyl cellulose at a lower concentration in the printing ink raw material solution can be monitored without destroying and changing the dissolution behavior of ethyl cellulose in the printing ink raw material solution, thereby improving the accuracy of evaluating the dissolution degree of ethyl cellulose in the printing ink raw material solution during baking; based on the numerical difference in the clarity of the printing ink raw material solution at the time before the current sampling time, it is judged whether the baking of the printing ink raw material solution needs to be stopped. The beneficial effect is that it realizes the control of the baking time in the printing ink preparation step, improves the quality of the prepared printing ink, and then improves the quality of the high-temperature resistant ceramic adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0045] Figure 1 A flowchart of the steps of a method for preparing a high temperature resistant ceramic adhesive based on parameter optimization provided in an embodiment of the present application;

[0046] Figure 2 A schematic diagram of Raman spectroscopy baseline correction provided in an embodiment of the present application;

[0047] Figure 3 A schematic diagram of Raman spectroscopy peak detection provided in an embodiment of the present application;

[0048] Figure 4 A peak intensity variation curve of ethyl cellulose provided in the examples of the present application;

[0049] Figure 5 A schematic diagram of obtaining the characteristic peak intensity sequence of ethyl cellulose and the characteristic peak width sequence of ethyl cellulose of pixel a provided in an embodiment of the present application;

[0050] Figure 6 A flowchart of the implementation process of real-time control of baking time provided in an embodiment of the present application. DETAILED DESCRIPTION

[0051] In order to further explain the technical means and effects adopted by the present application to achieve the predetermined invention purpose, the following is a detailed description of the preparation method of the high temperature resistant ceramic adhesive based on parameter optimization proposed in the present application, its specific implementation method, structure, characteristics and effects, in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "another embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0052] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.

[0053] The specific scheme of the preparation method of the high temperature resistant ceramic adhesive based on parameter optimization provided by the present application is described in detail below with reference to the accompanying drawings.

[0054] The preparation method of the high temperature resistant ceramic adhesive based on parameter optimization provided in the embodiment of the present application, please refer to the preparation flow chart Figure 1 , the specific preparation process is as follows:

[0055] Example 1

[0056] S1, synthetic powder preparation:

[0057] The raw material powders are dry mixed to ensure uniform distribution of the raw materials; the mixed raw material powders are sieved through a sieve to obtain finer powders; a 99 porcelain container is used to load the sieved powders into it and placed in a high-temperature electric furnace at 1000 The pre-synthesized powder was taken out of the electric furnace and placed in a nylon ball mill for ball milling to obtain more uniform and fine powder particles; the ball-milled mixture was heated at 60 The powder is dried at a temperature of 100°C for 12 hours to remove alcohol and other volatile components therein; the dried powder is sieved again to ensure that the particle size of the powder particles in the final synthetic powder is uniform, and the synthetic powder is obtained for standby use.

[0058] In this embodiment, the raw material powders and mass percentages of the synthetic powder are: 10% analytical pure aluminum oxide, 75% analytical pure silicon dioxide, 3% analytical pure magnesium oxide, 6% analytical pure potassium nitrate, and 3% analytical pure anhydrous sodium carbonate.

[0059] Among them, the ball milling treatment was carried out in the nylon ball mill according to the ratio of material: ball: alcohol = 1:2:1.

[0060] S2, ink preparation:

[0061] Put the raw materials for preparing printing ink into the container for heating and stir evenly to ensure that there is no lumps; put the container containing the printing ink raw material solution into the container preheated to 70 In the oven, the solid particles in the printing ink raw material solution will be heated and melted. The baking process lasts for about 12 hours until a clear printing ink raw material solution is obtained. The purpose of heating is to completely dissolve the ethyl cellulose in the printing ink raw material solution in pine oil. After the baking process is completed, the container is taken out of the oven and placed at room temperature for natural cooling. As the temperature decreases, the printing ink solution in the container will become more viscous, and the printing ink is obtained for use.

[0062] In this embodiment, the raw material ratio of the printing ink is: 1000 ml of analytically pure pinene alcohol, 40 grams of 200 mPa.S ethyl cellulose, and 20 grams of 50 mPa.S ethyl cellulose.

[0063] Since this application needs to decide whether to stop baking based on the clarity of the printing oil raw material solution, and the length of baking time may have a great impact on the quality of the printing oil. If the baking time is too short, the ethyl cellulose in the printing oil raw material solution may not have enough time to completely dissolve, so that the printing oil raw material solution fails to reach the required clarity, affecting the transparency and color of the printing oil, and if the baking time is too long, it may cause excessive evaporation of pine oil, affecting the viscosity of the final printing oil. However, human judgment of the clarity is prone to deviation, resulting in poor quality of the prepared printing oil. Accordingly, this embodiment analyzes the baking solution data information during the printing oil preparation process and controls the baking time in real time, thereby preparing a clear printing oil raw material solution. Specifically:

[0064] (1) Collect Raman spectral data of the ink raw material solution during the baking process of ink preparation, as well as Raman spectral data of ethyl cellulose and analytically pure pinene alcohol.

[0065] During the baking process of the printing ink preparation, this embodiment uses a Raman spectrometer equipped with a Raman fiber optic probe to collect data of the printing ink raw material solution in the container in the oven every 5 minutes, wherein the sampling time interval of the Raman spectrum data can be set by the implementer, and the Raman spectrum data of ethyl cellulose and analytical pure pinene alcohol are collected at the same time.

[0066] So far, the Raman spectrum data of the printing ink raw material solution at each sampling moment, as well as the Raman spectrum data of analytically pure pineneol and the Raman spectrum data of ethyl cellulose are obtained.

[0067] (2) Based on the data overlap distribution in the Raman spectral data of the printing ink raw material solution, analytically pure pinene alcohol and ethyl cellulose, the pixel category of any pixel in the Raman spectral data of the printing ink raw material solution is divided.

[0068] This embodiment is based on Raman spectral data of ink raw material solution at sampling time Pixels in For example, get the pixel In the data The Raman spectra in the image are corrected by using a baseline correction algorithm based on penalized least squares. The Raman spectrum is processed to remove pixels The baseline drift phenomenon that may exist in the Raman spectrum of the pixel The baseline correction algorithm based on penalized least squares is a well-known technology and the specific process will not be described in detail.

[0069] In this embodiment, the Raman spectrum baseline correction schematic diagram is as follows Figure 2 shown.

[0070] exist Figure 2 In the figure, the horizontal axis is the wave number position and the vertical axis is the Raman scattered light intensity.

[0071] Pixel The Raman scattered light intensity at each wave number position in the corrected Raman spectrum is arranged in ascending order of wave number position to obtain the pixel The Raman scattered light intensity sequence. Extract pixel All Raman spectral peaks in the corrected Raman spectrum are calculated, and the peak intensity and half-height width of each extracted Raman spectral peak are calculated, where each Raman spectral peak corresponds to a specific wavenumber position and Raman scattered light intensity, and the pixel The wavenumber positions of all Raman spectral peaks are in the pixel The corresponding data point in the Raman scattered light intensity sequence is assigned a value of 1, and the pixel The remaining data points in the Raman scattered light intensity sequence are assigned 0, and the reassigned sequence is recorded as pixel The peak sequence of Raman spectrum , to characterize the pixels The position distribution of all Raman spectral peaks in the Raman spectrum.

[0072] In this embodiment, the schematic diagram of Raman spectrum peak detection is as follows: Figure 3 shown.

[0073] exist Figure 3 In the figure, the horizontal axis is the wave number position, the vertical axis is the Raman scattered light intensity, and the cross position is the Raman spectrum peak in the corrected Raman spectrum.

[0074] Furthermore, using the pixel The Raman spectrum peak position sequence of each pixel in the Raman spectrum data of ethyl cellulose is obtained by the same method. All the obtained Raman spectrum peak position sequences of ethyl cellulose are averaged to obtain the Raman spectrum peak position enhancement sequence of ethyl cellulose. , in order to enhance the position distribution characteristics of the Raman spectrum peak in the Raman spectrum of ethyl cellulose. The averaging method is to The value of the data point is assigned to the peak position sequence of all Raman spectra of ethyl cellulose. The mean of the data points was calculated, and each data point was rounded off to ensure that the value of each data point in the obtained sequence was 0 or 1. The Raman spectrum peak position enhancement sequence of pure pinene alcohol was obtained by the same method. .

[0075] Since the Raman spectrum of each substance is unique, the Raman spectrum peaks in the Raman spectra of different substances appear at different wavenumber positions. For example, the Raman spectrum peak sequence is counted The number of data points that are the same as the number of data points in the Raman spectrum peak enhancement sequence of ethyl cellulose is recorded as the ratio of the statistical result to the number of data points in the Raman spectrum peak enhancement sequence of ethyl cellulose. The Raman peak overlap of ethyl cellulose , the Raman spectrum peak sequence The statistical results and sequence of the number of identical data points in the Raman spectrum peak enhancement sequence of analytical pure pinene alcohol The ratio of the number of data points in is recorded as pixel The Raman peak overlap of analytical pure terpineol .

[0076] It should be understood that when ethyl cellulose is combined with the pixel The greater the overlap of the wavenumber positions of the Raman spectral peaks in the Raman spectrum, the greater the pixel The more likely it is that the pixel corresponding to the ethyl cellulose substance in the printing ink raw material solution in the Raman spectrum data of the printing ink raw material solution is the pixel corresponding to the ethyl cellulose substance in the printing ink raw material solution. The greater the overlap of the wavenumber positions of the Raman spectral peaks in the Raman spectrum, the greater the pixel The more likely it is the pixel corresponding to the analytically pure pinepineol substance in the printing ink raw material solution in the Raman spectrum data of the printing ink raw material solution.

[0077] like , then the pixel The pixel is marked as ethyl cellulose, otherwise it is marked as analytical pure terpineol pixel. All pixels in are divided into ethyl cellulose pixels and analytical pure pineneol pixels respectively.

[0078] (3) The clarity of the printing ink raw material solution is determined based on the peak intensity and half-peak width of the Raman spectrum peaks corresponding to the ethyl cellulose pixels at different wavenumber positions in the Raman spectrum data of the printing ink raw material solution.

[0079] Generally speaking, as the degree of solubility of ethyl cellulose in the printing ink raw material solution increases, the peak intensity of the Raman spectral peak in the Raman spectrum of the pixel corresponding to ethyl cellulose in the Raman spectral data of the printing ink raw material solution will become stronger. This is because the distribution of the dissolved ethyl cellulose molecules in the solvent will be more uniform, which may lead to an increase in the number of molecules per unit volume, and the Raman scattering signal is proportional to the number of molecules, which will increase the peak intensity of a specific Raman spectral peak in the Raman spectrum of the ethyl cellulose pixel, and as the ethyl cellulose dissolves, the half-peak width of the Raman spectral peak may also increase. This is because after the solid particles in the solvent are dissolved, the interaction between the solvent and the solute, such as hydrogen bonding or van der Waals forces, may cause the vibration state of the solute molecules to be dynamically disturbed, resulting in an increase in the peak width.

[0080] In this embodiment, the peak intensity variation curve of ethyl cellulose is as follows: Figure 4 shown.

[0081] In the peak intensity variation curve of ethyl cellulose, the horizontal coordinate on the bottom plane is the wave number position, the vertical coordinate is the concentration of ethyl cellulose, and the vertical coordinate is the Raman scattered light intensity.

[0082] Based on the above analysis, the pixel For example, all data points with a median value of 1 in the Raman spectrum peak position enhancement sequence of pure pinene alcohol are analyzed in the Raman spectrum peak position sequence All data points at the corresponding positions in the image are assigned a value of 0 to eliminate the pixel The interference of the Raman spectrum peak of analytical pure pinene alcohol in the Raman spectrum of ethyl cellulose is prominent. The position distribution characteristics of the Raman spectrum peaks in the Raman spectrum are recorded as pixels. Characteristic peak sequence of ethyl cellulose .

[0083] In pixels For example, the sequence The peak intensity and half-peak width of the Raman spectrum peak corresponding to the wave number position of each data point with a value of 1 in the sequence The data points at the corresponding positions in are reassigned, and the assigned sequences are recorded as pixels. Characteristic peak intensity sequence of ethyl cellulose and ethyl cellulose characteristic peak width sequence .

[0084] In this embodiment, the pixel The schematic diagram of obtaining the characteristic peak intensity sequence and the characteristic peak width sequence of ethyl cellulose is shown in Figure 5 shown.

[0085] Use with sequence , In the same way, the sequence Replace with sequence , and obtain the peak intensity sequence of ethyl cellulose and peak width sequence .

[0086] Calculation sequence , The ratio between the data points at the same position in The data point in is 0, which causes the denominator to be 0. Each data point in , where the constant The value is 0.01, and the mean of all calculated ratios is recorded as the pixel Ethylcellulose peak intensity increase ; Use and increase The same method is used to obtain pixels Ethyl cellulose peak width increase , where the sequence , Replace with sequence , Then, With the increase The product of Solubility of ethylcellulose granules .

[0087] It should be understood that ethyl cellulose is The greater the intensity of the Raman spectrum peak in the Raman spectrum, the greater the amplification The larger the value, the wider the half-peak width of the Raman spectrum peak, and the greater the amplification The larger the value of The greater the solubility of the corresponding ethyl cellulose solid particles in the ink raw material solution, the higher the solubility The larger the value of .

[0088] Calculate the Raman spectral data of the ink raw material solution The average solubility of ethyl cellulose particles in all ethyl cellulose pixels in the The clarity of the printing ink raw material solution at the sampling time .

[0089] It should be understood that in The greater the overall dissolution degree of ethyl cellulose solid particles in the ink raw material solution at each sampling moment, the greater the data The larger the solubility value of the ethyl cellulose particles in the middle pixel, the At the sampling moment, the clearer the ink raw material solution is, The larger the value of .

[0090] (4) Based on the difference in the clarity of the printing ink raw material solution at a time before the current sampling time, it is determined whether the baking of the printing ink raw material solution needs to be stopped.

[0091] First Take the sampling moment as an example and calculate the arrive The clarity of the printing ink raw material solution at each sampling time during the sampling time period is The value is 10. , then let .

[0092] Calculate the coefficient of variation of the clarity of all ink raw material solutions and add the constant The inverse of the result is taken as the Baking completion coefficient at sampling time , where the constant This is to prevent the coefficient of variation from being zero and causing the denominator to be zero. The constant The value is 0.01.

[0093] It should be understood that in arrive During the sampling time, the closer the clarity values ​​of the printing ink raw material solutions are, and the greater the clarity values ​​of the printing ink raw material solutions are, the greater the clarity values ​​of the printing ink raw material solutions are. At the sampling moment, the more fully the solid particles of ethyl cellulose are dissolved in the printing ink raw material solution, the more it is necessary to stop baking at this time. The larger the value of .

[0094] A preset number of printing ink raw material solutions with clarity levels that meet the standards are obtained. The printing ink raw material solutions with clarity levels that meet the standards are obtained by manual judgment, and the printing ink raw material solutions with clarity levels that meet the standards are screened out. The average of the baking completion coefficients of all the printing ink raw material solutions with clarity levels that meet the standards at the last sampling moment during the baking process is used as the baking completion threshold. In this embodiment, the value of the preset number obtained is 10, and the implementer can set it according to the actual situation.

[0095] like , then the clarity of the printing ink raw material solution is If the sampling time meets the standard, the baking of the printing ink raw material solution can be stopped.

[0096] At this point, the baking time in the printing ink preparation step can be controlled according to the above steps.

[0097] S3, high temperature resistant ceramic adhesive preparation:

[0098] Add synthetic powder and printing oil into a nylon ball mill, and place the nylon ball mill containing the synthetic powder, printing oil and alcohol into a planetary mill for ball milling. The ball milling time is controlled at 5 hours. The planetary mill uses the rotation and vibration of the balls to fully mix and grind the synthetic powder and printing oil. After the ball milling is completed, sieve the mixture in the nylon ball mill through a 60-mesh sieve in a hot state to ensure that there are no coarse particles in the mixture, thereby obtaining a uniform and delicate paste, and the obtained paste is a high-temperature resistant ceramic adhesive.

[0099] In this embodiment, the raw materials and the proportion of the high temperature resistant ceramic adhesive are: 60 grams of synthetic powder and 70 grams of printing ink.

[0100] In this embodiment, the process flow chart of the implementation of real-time control of baking time is as follows: Figure 6 shown.

[0101] Example 2

[0102] The preparation of synthetic powder in step S1 of this embodiment is the same as that in embodiment 1. The raw material powders and mass percentages of the synthetic powder in this embodiment are: 20% analytical pure aluminum oxide, 50% analytical pure silicon dioxide, 2% analytical pure magnesium oxide, 8% analytical pure potassium nitrate, and 0% analytical pure anhydrous sodium carbonate.

[0103] The preparation of the printing ink in step S2 of this embodiment is the same as that in embodiment 1. The raw material ratio of the printing ink in this embodiment is: 1000 ml of analytically pure terpineol, 20 g of 200 mPa.S ethyl cellulose, and 10 g of 50 mPa.S ethyl cellulose.

[0104] In step S2 of preparing the printing ink in this embodiment, the real-time control method of the baking time is the same as that in embodiment 1.

[0105] The preparation of the high temperature resistant ceramic adhesive in step S3 of this embodiment is the same as that in embodiment 1. The raw materials and the proportion of the high temperature resistant ceramic adhesive in this embodiment are: 75 grams of synthetic powder and 50 grams of printing ink.

[0106] Example 3

[0107] The preparation of synthetic powder in step S1 of this embodiment is the same as that in embodiment 1. The raw material powders and mass percentages of the synthetic powder in this embodiment are: 15% analytical pure aluminum oxide, 60% analytical pure silicon dioxide, 5% analytical pure magnesium oxide, 2% analytical pure potassium nitrate, and 5% analytical pure anhydrous sodium carbonate.

[0108] The preparation of the printing ink in step S2 of this embodiment is the same as that in embodiment 1. The raw material ratio of the printing ink in this embodiment is: 1000 ml of analytically pure terpineol, 30 g of 200 mPa.S ethyl cellulose, and 30 g of 50 mPa.S ethyl cellulose.

[0109] In step S2 of preparing the printing ink in this embodiment, the real-time control method of the baking time is the same as that in embodiment 1.

[0110] The preparation of the high temperature resistant ceramic adhesive in step S3 of this embodiment is the same as that in embodiment 1. The raw materials and the proportion of the high temperature resistant ceramic adhesive in this embodiment are: 90 grams of synthetic powder and 80 grams of printing ink.

[0111] In summary, in all embodiments of the present application, the method of using the high-temperature resistant ceramic adhesive is as follows: the high-temperature resistant ceramic adhesive is evenly applied to the connection parts of the ceramic parts that need to be bonded together, and the vacuum cavity, air inlet, air outlet and cover plate are respectively processed for the ceramic parts, which can be applied manually. When applying the high-temperature resistant ceramic adhesive, the two or more ceramic parts that need to be bonded together need to be cleaned in advance and placed in an electric heating box. The two or more ceramic parts that need to be bonded together are dried. After drying, a small film or ceramic sheet is used to evenly apply the high-temperature resistant ceramic adhesive on the surface of the connection of the parts. The coated high-temperature resistant ceramic adhesive is light pink. The coated ceramic parts are then placed in an electric heating box, and the temperature of the electric heating box is adjusted to 130 degrees Celsius for baking to volatilize and solidify the organic matter in the high-temperature resistant ceramic adhesive. The high-temperature resistant ceramic adhesive after volatilization and solidification is milky white or light white. After drying, it is coated and baked again so that it is on the surface of the connection of the ceramic parts to be bonded. All of them have a uniform layer of milky white or light white high-temperature resistant ceramic adhesive. The thickness of the solidified high-temperature resistant ceramic adhesive is about 0.2mm. The high-temperature resistant ceramic adhesive can also be loaded into a plastic pot, and then a small hole is opened at the tip of the plastic pot lid. The diameter of the small hole is about 0.4mm. The plastic pot filled with high-temperature resistant ceramic adhesive is squeezed to make the adhesive flow out along the small hole at the tip of the plastic pot and evenly coated on the surface of the joint of the ceramic parts that need to be bonded together. It can also be coated manually or by screen printing. Since the high-temperature resistant ceramic adhesive has good fluidity, the coating method is flexible and varied. After more than two baking solidifications, two or more ceramic parts are put into a high-temperature furnace together for sintering. During sintering, the product is placed on a ceramic flat plate, and a ceramic pressing block is placed on the upper part of the product to make it bear downward force. When the temperature in the furnace rises to 1300 degrees Celsius, the ceramic parts will be tightly combined together, and will naturally drop to room temperature after 2 hours of insulation.

[0112] The ceramic products made by using the high temperature resistant ceramic adhesives described in all the embodiments of the present application were verified by experiments. The vacuum air ducts of the manufactured products were tested by a helium detector to achieve a completely leak-free effect. The high temperature environment test was carried out, and the manufactured products were placed in a high temperature furnace, the temperature of the high temperature furnace was raised to 800 degrees, and the products were taken out after 2 hours. The experiment was repeated 5 times, and the vacuum air ducts of the manufactured products were still leak-free. The ultra-high temperature resistant ceramic adhesive described in the present application can obtain products with excellent performance.

[0113] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0114] It should be noted that, unless otherwise specified and limited, terms such as "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a circuit structure, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such article or device. In the absence of further restrictions, an element defined by the sentence "including one..." does not exclude the existence of other identical elements in the article or device including the element. In addition, the term "and\or" used herein includes any and all combinations of one or more related listed items.

[0115] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the invention herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not invented by the present application.

[0116] It should be understood that the present application is not limited to the exact construction that has been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof.

Claims

1. A method for preparing a high temperature resistant ceramic adhesive based on parameter optimization, characterized in that: The method comprises the following steps: S1, preparation of synthetic powder: dry-mixing and sieving the raw powder; putting the sifted powder into a 99 porcelain container and placing it in a high-temperature electric furnace for pre-synthesis; placing the pre-synthesized powder into a nylon ball mill for ball milling, drying and sieving the ball-milled mixture to obtain synthetic powder for standby use; S2, preparing the printing ink: putting the raw materials for preparing the printing ink into a container, stirring evenly, and baking until a clear printing ink raw material solution is obtained; cooling the container to obtain the printing ink for use; wherein the specific steps of real-time control of the baking time are: (1) Collecting Raman spectral data of the ink raw material solution during the baking process of ink preparation, as well as Raman spectral data of ethyl cellulose and analytically pure pinene alcohol; (2) Based on the data overlap distribution in the Raman spectral data of the printing ink raw material solution, analytically pure pinene alcohol and ethyl cellulose, the ethyl cellulose pixels in the Raman spectral data of the printing ink raw material solution are divided; (3) determining the clarity of the printing ink raw material solution based on the peak intensity and half-peak width of the Raman spectrum peak corresponding to the ethyl cellulose pixel at different wavenumber positions in the Raman spectrum data of the printing ink raw material solution; (4) judging whether it is necessary to stop baking the printing ink raw material solution based on the difference in the clarity of the printing ink raw material solution at the time before the current sampling time; S3, preparation of high temperature resistant ceramic adhesive: adding synthetic powder and printing ink into a nylon ball mill, ball milling and sieving to obtain a high temperature resistant ceramic adhesive; The judgment conditions for whether the ink raw material solution needs to stop baking include: Calculate the coefficient of variation of the clarity of all printing ink raw material solutions obtained between the current sampling moment and the preset moment before, and use the reciprocal of the coefficient of variation at the current sampling moment as the baking completion coefficient at the current sampling moment; Obtain a preset number of printing ink raw material solutions whose clarity meets the standard; wherein the printing ink raw material solutions whose clarity meets the standard are obtained by manual judgment; The average value of the baking completion coefficients of all printing ink raw material solutions whose clarity meets the standard at the last sampling moment in the baking process is used as the baking completion threshold; If the baking completion coefficient at the current sampling moment is greater than the baking completion threshold, the baking of the printing ink raw material solution is stopped; The division process of the ethyl cellulose pixels in the Raman spectrum data of the printing ink raw material solution includes: For each pixel in the Raman spectrum data of the printing ink raw material solution, ethyl cellulose and analytically pure pinene alcohol, based on the Raman spectrum peak distribution in the corrected Raman spectrum of each pixel, determine the Raman spectrum peak position sequence of each pixel; All Raman spectrum peak position sequences of ethyl cellulose are averaged to obtain the Raman spectrum peak position enhancement sequence of ethyl cellulose; all Raman spectrum peak position sequences of analytically pure terpineol are averaged to obtain the Raman spectrum peak position enhancement sequence of analytically pure terpineol; For any pixel in the Raman spectrum data of the printing ink raw material solution, the statistical result of the number of identical data points in the Raman spectrum peak position sequence of the any pixel and the Raman spectrum peak position enhancement sequence of ethyl cellulose is counted, and the ratio of the number of data points in the Raman spectrum peak position enhancement sequence of ethyl cellulose is recorded as the Raman peak overlap of ethyl cellulose in the any pixel; the statistical result of the number of identical data points in the Raman spectrum peak position sequence of the any pixel and the Raman spectrum peak position enhancement sequence of analytically pure pinene alcohol is counted, and the ratio of the number of data points in the Raman spectrum peak position enhancement sequence of analytically pure pinene alcohol is recorded as the Raman peak overlap of analytically pure pinene alcohol in the any pixel; Classify any pixel whose Raman peak overlap of ethyl cellulose is greater than that of analytically pure pinene alcohol as an ethyl cellulose pixel; The method for determining the clarity of the printing ink raw material solution comprises: Assign values ​​of 0 to all data points at corresponding positions in the Raman spectrum peak position sequence of any pixel for all data points with a value of 1 in the peak position enhancement sequence of the Raman spectrum of the analytically pure terpineol, thereby obtaining a characteristic peak position sequence of ethyl cellulose of any pixel; Re-assign the peak intensity and half-peak width of the Raman spectrum peak corresponding to the wave number position of each data point with a value of 1 in the characteristic peak position sequence of ethyl cellulose of any pixel, and record the assigned sequences as the characteristic peak intensity sequence and the characteristic peak width sequence of ethyl cellulose of any pixel, respectively; Using the same method as the characteristic peak intensity sequence and the characteristic peak width sequence of ethyl cellulose of any pixel, the characteristic peak position sequence of ethyl cellulose of any pixel is replaced with the Raman spectrum peak position enhancement sequence of ethyl cellulose to obtain the spectrum peak intensity sequence and the spectrum peak width sequence of ethyl cellulose; Determine the ethyl cellulose peak width increase of any pixel based on the ethyl cellulose characteristic peak intensity sequence and the ethyl cellulose characteristic peak width sequence of any pixel, and the spectral peak peak intensity sequence and the spectral peak peak width sequence of ethyl cellulose; Calculating the average solubility of ethyl cellulose particles of all ethyl cellulose pixels in the Raman spectrum data of the printing ink raw material solution as the clarity of the printing ink raw material solution; The method for determining the ethyl cellulose peak width increase comprises: Calculate the cumulative sum of the ratios between the characteristic peak intensity sequence of ethyl cellulose of any pixel and all corresponding position data points in the peak intensity sequence of the spectrum peak of ethyl cellulose as the peak intensity increase of ethyl cellulose of any pixel; Calculate the cumulative sum of the ratios between the characteristic peak width sequence of ethyl cellulose of any pixel and all corresponding position data points in the peak width sequence of the spectral peak of ethyl cellulose as the peak width increase of ethyl cellulose of any pixel; The product of the ethyl cellulose peak intensity increase and the ethyl cellulose peak width increase of any pixel is taken as the ethyl cellulose particle solubility of any pixel.

2. The method for preparing a high temperature resistant ceramic adhesive based on parameter optimization according to claim 1, characterized in that: The raw materials and their mass percentages of the synthetic powder prepared in S1 are: analytical pure aluminum oxide 10 20%, analytical pure silica 50 75%, analytical pure magnesium oxide 2 5%, analytical pure potassium nitrate 2 8%, analytical pure anhydrous sodium carbonate 0 5%.

3. The method for preparing a high temperature resistant ceramic adhesive based on parameter optimization according to claim 1, characterized in that: The ratio of material, balls and alcohol in the nylon ball mill in S1 is 1:2:

1.

4. The method for preparing a high temperature resistant ceramic adhesive based on parameter optimization according to claim 1, characterized in that: The raw materials and proportions of the printing ink prepared in S2 are: 1000ml of analytically pure pinene alcohol, 200mPa.S of ethyl cellulose, 20 40g, 50mPa.S ethyl cellulose 10 30 grams.

5. The method for preparing a high temperature resistant ceramic adhesive based on parameter optimization according to claim 1, characterized in that: The method for determining the Raman spectrum peak sequence comprises: Acquire a corrected Raman spectrum of the Raman spectrum of each pixel using a baseline correction algorithm; Combining the Raman scattered light intensities of all wavenumber positions in the corrected Raman spectrum of each pixel into a Raman scattered light intensity sequence of each pixel; Obtaining a Raman spectrum peak in the corrected Raman spectrum of each pixel, and obtaining a wavenumber position and a Raman scattered light intensity corresponding to each Raman spectrum peak; The elements at the wavenumber positions corresponding to the Raman spectrum peak of each pixel in the Raman scattered light intensity sequence are assigned 1, and the remaining elements are assigned 0, and the sequence after the assignment is recorded as the Raman spectrum peak position sequence of each pixel.

6. The method for preparing a high temperature resistant ceramic adhesive based on parameter optimization according to claim 1, characterized in that: The ratio of synthetic powder and printing ink of the high temperature resistant ceramic adhesive in S3 is: synthetic powder 60 90g, printing ink 50 80 grams.

Citation Information

Patent Citations

  • Ceramic bond cubic boron nitride abrasive tool and manufacturing method thereof

    CN102826854A

  • Preparation method of silk-screen printing paste for ceramic sealing

    CN113979673A

  • Method of Evaluating Polymide Dissolution Rate, Method of Producing Polymide, and Polymide Obtained Using Same Methods

    US20090192287A1